Science teacher identity research: a scoping literature review - Yanfang Zhai; Jennifer Tripp; Xiufeng Liu (SpringerOpen, 2024)
Abstract Science teacher identity significantly influences teacher professional development, practices, and attitudes, which in turn impacts student learning outcomes. With an increased number of studies on science teacher identity over the past two decades, there is a need for a scoping literature review that holistically maps the current state of science teacher identity research and identifies future research directions. This scoping literature review identified 48 empirical articles on science teacher identity, published from 2000 to 2023, in peer-reviewed journals and examined the studies' (a) characteristics; (b) theoretical frameworks on identity; (c) definitions of science teacher identity; and (d) major findings. Specifically, there is a need for precise conceptualizations and definitions of science teacher identity; this clarity will facilitate valid, reliable, and fair instruments to capture the relatively stable facets of science teacher identity at a given moment in a given context in order to longitudinally track science teacher identity development. This scoping review identifies both progress and gaps in the current literature and future directions for synergistic, cross-cultural international research on science teacher identity.